2013
DOI: 10.3390/ijerph10041489
|View full text |Cite
|
Sign up to set email alerts
|

Sick Building Syndrome by Indoor Air Pollution in Dalian, China

Abstract: This study assessed subjective symptoms related to indoor concentrations of chemicals among residents in a housing estate in Dalian, China, where indoor air pollution by interior decoration materials has recently become a major health problem. Fifty-nine males and 50 females were surveyed for their symptoms related to sick building syndrome. Formaldehyde (HCHO), NO2, and volatile organic compounds (VOCs) in their dwellings were collected using a diffusion sampler and measured by GC/MS. For residents with one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 18 publications
2
27
1
1
Order By: Relevance
“…Formaldehyde can be emitted from indoor sources but can also be formed at photochemical reactions in the outdoor air (Guo et al, 2004). We found no previous study on associations between formaldehyde levels in schools and SBS symptoms among students, but some previous studies have found association between formaldehyde levels in homes and SBS-symptoms (Sahlberg et al, 2013;Guo et al, 2013;Takigawa et al, 2010;Takigawa et al, 2012), but at much higher levels than in our school study. It could be speculated that the source of formaldehyde in our study could be reactive indoor or outdoor chemistry.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Formaldehyde can be emitted from indoor sources but can also be formed at photochemical reactions in the outdoor air (Guo et al, 2004). We found no previous study on associations between formaldehyde levels in schools and SBS symptoms among students, but some previous studies have found association between formaldehyde levels in homes and SBS-symptoms (Sahlberg et al, 2013;Guo et al, 2013;Takigawa et al, 2010;Takigawa et al, 2012), but at much higher levels than in our school study. It could be speculated that the source of formaldehyde in our study could be reactive indoor or outdoor chemistry.…”
Section: Discussioncontrasting
confidence: 55%
“…One larger study in newly built dwellings in six prefectures from northern to southern Japan found that formaldehyde, but not specific VOC or TVOC, were associated with SBS (Takigawa et al, 2010). One study from Dalian, China, found positive associations between 1,1,1-trichloroethane, xylene, butanol, methyl isobutyl ketone, and styrene concentrations in homes and current SBS (Guo et al, 2013). Another study from Taiwan found associations between TVOC and upper respiratory symptoms, dry throat and mucosal irritation (Lu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For three air condition classrooms (S7-43D-R1, S7-43D-R2 and PJ-KD6-R1), mean indoor temperature were lower than the corresponding outdoor levels. However, the whole classrooms and respective outdoors stated higher value of mean temperature than the recommended range for acceptable indoor air quality of American Society of Heating, Refrigerating and Air-conditioning Engineers [18] at 23.0°C to 26°C. The I/O for temperature of each classroom stated in small value, range between 0.93-1.11.…”
Section: Iaq Characteristicsmentioning
confidence: 99%
“…The I/O for temperature of each classroom stated in small value, range between 0.93-1.11. Generally, relative humidity in four natural ventilation classrooms (S7-43D-R3, SP15-R1, SP15-R2 and KS-SU3-R1) exceeded the [18] recommendation limit at 30%-65%. The I/O relative humidity of each classroom have shown in small ranging, except the air-condition classroom PJ-KD6-R2 at 0.76 with the lowest ratio indoor-outdoor, suggesting that the mechanical air-conditioner have controlled the indoor environment.…”
Section: Iaq Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation